Pelatihan Assesment untuk Pembelajaran Blended Learning Memanfaatkan Socrative di MTS Laboratorium Kota Jambi - Winarni, Sri; Kumalasari, Ade; Marlina, Marlina; Junita, Ranisa; Rohati, Rohati (Fakultas Sains dan Teknologi, Universitas Jambi, 2023)
Online computer-based assessments will make it easier for teachers to conduct evaluations quickly and correctly. The time and costs required to prepare for exam activities can be reduced as effectively and minimally as possible. Online assessment applications that teachers can use include Socrative. Socrative software allows teachers to get immediate feedback from all students by downloading a free app to their phones. After the teacher formulates the question, the system will capture the student's answer and immediately produce graphs and statistics, which makes it easier for the teacher to evaluate the level of understanding of the concept being explained. This service aims to train teachers to use the Socrative application to make assessments in blended learning. The service activity is assessment training using Socrative for teachers in blended learning. The results of this service in the form of training show that teachers at MTs Laboratory have gained new insights regarding making assessments in blended learning and are very interested in implementing them in learning.